WTO Litigation and SEZs: Determining the Scope of Exceptional Trade Unilateralism. (4th May 2021) - Nedumpara, James J; Gupta, Manya; Choukroune, Leïla
ABSTRACT: The incentives available to enterprises located in special economic zones can be classified into three broad categories, namely, (i) fiscal incentives in the nature of tax incentives and exemption of duties, (ii) non-fiscal incentives in the form of infrastructural and developmental facilities, and (iii) regulatory incentives covering lenient and flexible compliance requirements. The fiscal incentives in special economic zones are, to an extent, regulated by the law of the World Trade Organization although direct challenges of special economic zone policies have been very few or non-existent. The absence of legal challenges led to a number of World Trade Organization members pursuing unilateral trade policies within their special economic zones. However, the recent World Trade Organization Panel findings in India—Export Related Measures appear to highlight the thin margin for trade unilateralism especially in relation to fiscal incentives in special economic zones. In the above context, this article examines the permissible limits of trade unilateralism, in the context of special economic zones, by providing a fresh understanding of the disciplines under international trade law and the available jurisprudence. It focuses, in particular, on the precise contours of permissible trade unilateralism exercised by World Trade Organization members when granting fiscal incentives. In doing so, this article also examines the concept of exception as a manifestation of unilateralism in International Economic Law.